Production of rhamnolipid biosurfactant by Pseudomonas aeruginosa using sunflower oil and glucose as carbon sources - Baharun, Sarinah (2015)
Biosurfactants are surface active compounds and amphiphatic in nature which consist of hydrophilic head and hydrophobic tail. These properties allow them to accumulate at the interphase of two immiscible liquid with different polarity such as in oil/water system and reducing surface and interfacial tension to facilitate emulsification. Rhamnolipids are biosurfactants produced by Pseudomonas sp. that offer significant advantageous over synthetic surfactants. Its production become increasingly throughout the years, however, the production yield was very low which discourage investment in this field. Therefore, a study was conducted to investigate the effectiveness of sunflower oil and glucose in the production of rhamnolipids by Pseudomonas aeruginosa in shake flask fermentation. In this process, four different fermentation treatments were done for seven days at 30°C under 180rpm. The sampling was carried out in appropriate time intervals (24 hours) and monitored for cell growth and the rhamnolipids production. Colorimetric Orcinol analysis was used for the determination of rhamnolipids concentrations. The produced rhamnolipids were studied for emulsification activity against hydrophobic substrate by using emulsification index (E24%) methods. In addition, oil displacement activity and the thermal stability were also studied over a wide range of temperature (4°C - 120°C). All treatments allow the growth of Pseudomonas aeruginosa, however the utilisation of sunflower oil as carbon source (addition at 8 hours) and glucose as growth initiator were observed to be the best strategy for maximum rhamnolipids production. The maximum rhamnolipids production was achieved after 120 hours with 3.18 g/L of rhamnolipids. Diesel shows the highest emulsification activity among the substrate tested ranging from 55.56% - 60.00%. The oil displacement activity was correspond to rhamnolipids concentration and very good stability which up to 120°C (for 60 minutes). Therefore, from this research a good potential of rhamnolipids biosurfactants that may provide good application for industrial were successfully produced.